2011
DOI: 10.1111/j.1365-2265.2011.04035.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of osteocalcin, procollagen type 1 N-terminal propeptide and beta-CrossLaps in obese subjects with varying degrees of glucose tolerance

Abstract: Obese patients with T2D showed significantly reduced levels of OC in comparison with patients with lower degrees of glucose tolerance derangement. Our results also suggest that OC was the only bone marker independently related to the degree of glucose metabolism derangement in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 21 publications
10
45
3
2
Order By: Relevance
“…Increased BMI is associated with reduced bone turnover markers (BTM) and increased aBMD [17,18]. Similar observations with glucose-loading have been made in healthy subjects [15].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Increased BMI is associated with reduced bone turnover markers (BTM) and increased aBMD [17,18]. Similar observations with glucose-loading have been made in healthy subjects [15].…”
Section: Introductionsupporting
confidence: 65%
“…Increased cortical porosity of distal radius or distal tibia has been invoked as one possible factor [11][12][13]. However, it is hard to explain how individuals with T2DM can exhibit high porosity [14][15][16][17], since increased cortical porosity reflects increased bone turnover from intracortical surfaces lining the Haversian canals and the endocortical surfaces adjacent to the marrow cavity [18,19]. As T2DM is a condition with low bone turnover [20,21], patients with T2DM would rather be expected to exhibit reduced cortical porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, osteocalcin was inversely associated with plasma glucose, insulin levels, and serum triglycerides in elderly men and women as well as elderly men with high cardiovascular risk (183,184,185,186,187,188). Also, osteocalcin was lower in patients with T2DM (189,190,191) and gestational diabetes (192).…”
Section: Metabolic Aspects In Relation To a Homeostatic Model Involvimentioning
confidence: 90%
“…Recent human studies have also shown a relationship between OC and fat and carbohydrate metabolism [11,12]. Osteocalcin has been reported to be decreased in patients with type 2 diabetes [13,14], negatively correlated with fasting plasma glucose, HbA 1c , insulin resistance, C-reactive protein and BMI [15,16], and increased with improved glycaemic control [12,17]. There is increasing evidence that serum osteocalcin level is associated with the presence of metabolic syndrome [18,19].…”
Section: Discussionmentioning
confidence: 99%